The effect of magnesium sulphate on clinical outcomes of low-birth-weight babies at the Chris Hani Baragwanath Academic Hospital - Odubunmi, Temitope Olawale Oluwadare (My University, 2024)
Introduction Magnesium sulphate (MgSO4) has been used for neuroprotection in the management of preeclamptic toxaemia (PET) and eclampsia in mothers of neonates at a lower gestational age and its’ use is recommended in preterm deliveries less than 30-32 weeks of gestation. There may be greater effects at an earlier gestational age, with no associated long term adverse foetal or maternal effects; resulting in increased survival of preterm babies. The aim of the study was to assess if the administration of MgSO4 improved the neonatal outcomes in low birth weight (LBW) infants whose mothers received magnesium sulphate. Methods This was a retrospective descriptive study of neonates, whose mothers’ received MgSO4 (as indicated by MgSO4+ group) admitted to the neonatal unit within a two-year period (January 2016 – December 2017). The demographics and outcome at hospital discharge were collected and analysed. Results A total of 485 (7.5%) of 6510 LBW neonates’ mothers received MgSO4. Pre-eclamptic toxaemia (PET) [n=235 (48%)], eclampsia [n=90 (19%)] and Haemolysis, Elevated Liver enzymes, Low platelets (HELLP) syndrome [n=28 (6%)] were the main indicators for the administration of MgSO4. Mothers in the MgSO4+ group were older and had a higher parity. Seventy percent received antenatal steroids in the MgSO4+ group and 30% of these were HIV positive. Neonates in the MgSO4+ group had a lower gestational age (p < 0.001) and birthweight (p<0.001). A smaller number of neonates in the MgSO4+ group required resuscitation and had higher oxygenation (p=0.005) on admission. A higher proportion of neonates in the MgSO4+ group had lethargy, hypotonia (p<0.001), asphyxia (p<0.001), early onset sepsis (EOS) (p<0.001), intraventricular haemorrhage (IVH) (p<0.001), respiratory distress syndrome (RDS) (p<0.001), required respiratory support (p<0.001) and died (p<0.001). In the multivariate logistic regression analysis; PET, asphyxia and hypotonia were associated with mortality. Conclusion There was an increase in neonatal morbidities and mortality in neonates whose mothers received MgSO4+. Monitoring of these neonates, in addition to monitoring MgSO4+ levels to document a dose effect, is essential
A research report submitted in partial fulfilment of the requirement for the degree of Master of Medicine (MMed) in Paediatrics to the Faculty of Health Sciences, University of the Witwatersrand, School of Clinical Medicine, Johannesburg, 2023
Keywords: Neonate; Low birth weight; Magnesium sulphate; Pre-eclamptic toxaemia; SDG-3: Good health and well-being